Non-target effect of pesticides in rice environment - G, Basana Gowda; Ray, Aishwarya; Adak, Totan; Sahu, Madhusmita; Sahu, Nandini; Pandi, Guru Pirasanna; Patil, Naveenkumar B.; M, Annamalai; Rath, Prakash Chandra (ORYZA-An International Journal of Rice, 2021)
Agriculture has always been affected by intractable pests. Conventional agriculture still relies on the use ofÂ several pesticides to control various pests to ensure the yield of the crop and to feed a constantly growingÂ population. To reduce the pest menace, the fatuous behavior of people as well as a natural proclivity towardsÂ the use of pesticides in a non-judicious manner, has caused several ecological backlashes such as secondaryÂ pest outbreak, pest resurgence and non-target organism’s exploitation. Effects of pesticides on non-target organisms area worldwide concern and contention are the basis for most legislation regarding usage of specificÂ pesticides. Pesticides, besides their effect on pests, would also affect several beneficial non-targets. The effect ofÂ pesticides could be lethal and may prove catastrophic or sublethal and stimulate the growth and developmentÂ of non targeted biota’s. Hence, this review approaches well-analyzed hindsight regarding the effect of pesticidesÂ on the natural enemies as well as other non-target organisms present in the rice agroecosystem.